Cerebral Air Embolism: A Clinical, Radiologic and Histopathologic Correlation. (December 2016) - Roquero, Leonardo Pacheco; Camelo-Piragua, Sandra; Schmidt, Carl
Abstract : Abstract: Cerebral air embolism is a recognized life-threatening complication, sometimes iatrogenic. Its timely diagnosis is essential because it can result in neurologic deficits or death. We report a case of a 58-year-old man who died from cerebral air embolism diagnosed by nonenhanced computed tomography scan of the head after a cardiac bypass surgery with Biventricular Assist Device and multiple vascular line placements. Autopsy revealed extensive subcutaneous emphysema, intravascular and perivascular air bubbles in the central nervous system and associated cerebral and cerebellar hemorrhagic infarction. The autopsy was helpful in documenting the extent of the air embolism and its appearance in soft tissue and central nervous system.